2019
DOI: 10.1093/cvr/cvz187
|View full text |Cite
|
Sign up to set email alerts
|

ADAMTS16 activates latent TGF-β, accentuating fibrosis and dysfunction of the pressure-overloaded heart

Abstract: Aims Cardiac fibrosis is a major cause of heart failure (HF), and mediated by the differentiation of cardiac fibroblasts into myofibroblasts. However, limited tools are available to block cardiac fibrosis. ADAMTS16 is a member of the ADAMTS superfamily of extracellular protease enzymes involved in extracellular matrix (ECM) degradation and remodelling. In this study, we aimed to establish ADAMTS16 as a key regulator of cardiac fibrosis. Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
61
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 69 publications
(64 citation statements)
references
References 60 publications
(88 reference statements)
2
61
1
Order By: Relevance
“…Depending on contextual factors, the type of injury, and the cell biological composition of the tissue, several different pathways may play a role in TGF-β activation in fibrotic tissues. First, a number of proteases, including calpains, cathepsins, serine proteases, matrix metalloproteinases (MMPs), and members of the ADAMTS (a disintegrin and metalloproteinase with thrombospondin motifs) family, are capable of activating TGF-β in vitro and may be implicated in TGF-β activation in fibrotic lesions in vivo ( Shea et al, 2017 ; Briassouli et al, 2011 ; Bourd-Boittin et al, 2011 ; Edgtton et al, 2004 ; Okuno et al, 2001 ; Khalil et al, 1996 ; Yao et al, 2019 ). Considering the promiscuity of these proteases, which are capable of interacting with numerous substrates, the relative significance of their TGF-β–activating effects remains poorly understood.…”
Section: Induction and Activation Of Tgf-β In Tissue Injury And Fibromentioning
confidence: 99%
“…Depending on contextual factors, the type of injury, and the cell biological composition of the tissue, several different pathways may play a role in TGF-β activation in fibrotic tissues. First, a number of proteases, including calpains, cathepsins, serine proteases, matrix metalloproteinases (MMPs), and members of the ADAMTS (a disintegrin and metalloproteinase with thrombospondin motifs) family, are capable of activating TGF-β in vitro and may be implicated in TGF-β activation in fibrotic lesions in vivo ( Shea et al, 2017 ; Briassouli et al, 2011 ; Bourd-Boittin et al, 2011 ; Edgtton et al, 2004 ; Okuno et al, 2001 ; Khalil et al, 1996 ; Yao et al, 2019 ). Considering the promiscuity of these proteases, which are capable of interacting with numerous substrates, the relative significance of their TGF-β–activating effects remains poorly understood.…”
Section: Induction and Activation Of Tgf-β In Tissue Injury And Fibromentioning
confidence: 99%
“…Thus, ADAMTS16 was suggested to be involved in degradation of the basement membrane at the optic fissure edges, the prerequisite for optic fissure closure ( 44 ). ADAMTS16 was further shown to be an activator of the latent transforming growth factor-β signaling ( 55 ). Concerted regulation of the transforming growth factor-β signaling pathway is crucial for embryonic development, as for instance for the morphogenesis of the eye ( 56 , 57 ).…”
Section: Discussionmentioning
confidence: 99%
“…Hein et al found that expression of TGF-β was closely related to the degree of myocardial fibrosis in patients with compensatory cardiac hypertrophy that progressed to heart failure [ 22 ]. Studies on animal models have shown that TGF-β overexpression causes interstitial fibrosis and cardiac hypertrophy [ 23 ]. A consensus from an international forum on cardiac remodeling noted that elevated LVEDV and decreased LVEF occur in post-infarction LVR [ 24 ].…”
Section: Discussionmentioning
confidence: 99%